India - Rural governments and Service Delivery : Volume 2. Note - World Bank (Washington, DC, 2012)
This study addresses the roles of different levels of government and the institutional arrangements involved in the provision of key services. The focus throughout is on disadvantaged rural areas. The study demonstrates the approach for a small number of sectors that have been "devolved" to rural governments (panchayats), but it is immediately applicable to any other sector of the 29 subjects eligible for devolution. The study intends to assist the Government of India and state governments in defining the role of panchayats in the delivery of key services to rural people. The study focuses on Kerala, Karnataka, West Bengal and Rajasthan; four states that cover a range of situations in India. Since the assignment of responsibilities to local governments is a state responsibility and Indian states have followed different approaches. All four states examined by this study have shown commitment to devolution in principle, but they differ considerably in the characteristics and pace of reforms. It is a study on what the various levels of panchayats could do in the delivery of these services within the decentralized government structure created by the 1993 Amendment to the constitution of India.